Transcriptome Reveals Long Non-coding RNAs and mRNAs Involved in Primary Wool Follicle Induction in Carpet Sheep Fetal Skin - Nie, Yangfan; Li, Shaomei; Zheng, XinTing; Chen, Wenshuo; Li, Xueer; Liu, Zhiwei; Hu, Yong; Qiao, Haisheng; Qi, Quanqing; Pei, Quanbang; Cai, Danzhuoma; Yu, Mei; et al. (Frontiers in Physiology, 2018)
Murine primary hair follicle induction is driven by the communication between the mesenchyme and epithelium and mostly governed by signaling pathways including wingless-related integration site (WNT), ectodysplasin A receptor (EDAR), bone morphogenetic protein (BMP), and fibroblast growth factor (FGF), as observed in genetically modified mouse models. Sheep skin may serve as a valuable system for hair research owing to the co-existence of sweat glands with wool follicles in trunk skin and asynchronized wool follicle growth pattern similar to that of human head hair follicles. However, the mechanisms underlying wool follicle development remain largely unknown. To understand how long non-coding RNAs (lncRNAs) and mRNAs function in primary wool follicle induction in carpet wool sheep, we conducted high-throughput RNA sequencing and revealed globally altered lncRNAs (36 upregulated and 26 downregulated), mRNAs (228 elevated and 225 decreased), and 80 differentially expressed novel transcripts. Several key signals in WNT (WNT2B and WNT16), BMP (BMP3, BMP4, and BMP7), EDAR (EDAR and EDARADD), and FGF (FGFR2 and FGF20) pathways, and a series of lncRNAs, including XLOC_539599, XLOC_556463, XLOC_015081, XLOC_1285606, XLOC_297809, and XLOC_764219, were shown to be potentially important for primary wool follicle induction. GO and KEGG analyses of differentially expressed mRNAs and potential targets of altered lncRNAs were both significantly enriched in morphogenesis biological processes and transforming growth factor-β, Hedgehog, and PI3K-Akt signaling, as well as focal adhesion and extracellular matrix-receptor interactions. The prediction of mRNA-mRNA and lncRNA-mRNA interaction networks further revealed transcripts potentially involved in primary wool follicle induction. The expression patterns of mRNAs and lncRNAs of interest were validated by qRT-PCR. The localization of XLOC_297809 and XLOC_764219 both in placodes and dermal condensations was detected by in situ hybridization, indicating important roles of lncRNAs in primary wool follicle induction and skin development. This is the first report elucidating the gene network of lncRNAs and mRNAs associated with primary wool follicle early development in carpet wool sheep and will shed new light on selective wool sheep breeding.